2009
DOI: 10.1007/s00294-009-0281-7
|View full text |Cite
|
Sign up to set email alerts
|

Histone modifying proteins Gcn5 and Hda1 affect flocculation in Saccharomyces cerevisiae during high-gravity fermentation

Abstract: The performance of yeast is often limited by the constantly changing environmental conditions present during high-gravity fermentation. Poor yeast performance contributes to incomplete and slow utilization of the main fermentable sugars which can lead to flavour problems in beer production. The expression of the FLO and MAL genes, which are important for the performance of yeast during industrial fermentations, is affected by complex proteins associated with Set1 (COMPASS) resulting in the induction of floccul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Previous reports have connected Cyc8–Tup1 to class I histone deacetylases (HDACs) Rpd3p and Hos2p [31] , and Tup1p has been linked to the class II HDAC Hda1p [33] . Flocculation was also reported to be induced during high-gravity fermentation in an hda1 mutant [60] . In order to identify which HDACs, if any, were involved in FLO1 gene repression in our system, mutations in various HDACs were prepared and screened for FLO1 transcription.…”
Section: Resultsmentioning
confidence: 92%
“…Previous reports have connected Cyc8–Tup1 to class I histone deacetylases (HDACs) Rpd3p and Hos2p [31] , and Tup1p has been linked to the class II HDAC Hda1p [33] . Flocculation was also reported to be induced during high-gravity fermentation in an hda1 mutant [60] . In order to identify which HDACs, if any, were involved in FLO1 gene repression in our system, mutations in various HDACs were prepared and screened for FLO1 transcription.…”
Section: Resultsmentioning
confidence: 92%
“…It was proposed that COMPASS was involved in silencing the expression of FLO1 , FLO5 and FLO9 genes (Dietvorst and Brandt 2008). Recently, it was shown that in addition to COMPASS, the histone deacetylase (Hda1) and histone acetyltransferase (Gcn5) proteins are required to repress FLO genes in high‐gravity fermentations (Dietvorst and Brandt 2010). Histone deacetylases (HDACs) are transcriptional repressors; they reduce acetylation of histones, creating regions of repressed chromatin.…”
Section: Genetic Basis Of Flocculationmentioning
confidence: 99%
“…Other histone modification enzymes, like Gcn5, have also been shown to be involved in silencing. FLO1 gene is expressed in the absence of Had1, whereas the expression of FLO1 and FLO9 genes is induced in the absence of Gcn5 (Dietvorst and Brandt 2010).…”
Section: Genetic Basis Of Flocculationmentioning
confidence: 99%
“…Flocculation is governed by FLO genes and quite a few flocculation activators and suppressor genes have been described in literature[11]. FLO genes appears to be regulated by upstream genetic elements where different activator and repressor proteins are known to bind including Set1 (COMPASS) methylation complex[55] and Histone deacetylases (HDACs) such as Gcn5p, Had1[56]; however, the mechanisms that control this complex process is not fully understood. Our current study sheds light on the process of flocculation control by identifying Sen1p as a novel regulator.…”
Section: Discussionmentioning
confidence: 99%